The Effect of Causalitic Learning Model Integrated with Character Values on Creative Thinking Ability of Student - Sri Khairani; Hikmawati; Joni Rokhmat; Kosim (International Journal of Contextual Science Education, 2024)
The purpose of this study was to investigate how the capacity for creative thinking is affected by the integration of causal learning model with character value learning. Quasi-experiment with untreated control group design and pretest-posttest methodology was the research design used. The research population amounted to 52 people, all of whom were students of class XI IPA SMAN 2 Labuapi. Saturated sampling was used in the research sample, by setting class X1 IPA 1 as the experimental class and class X1 IPA 2 as the control class. The control class received teaching using the traditional learning model, while the experimental class received teaching using the causal learning model combined with character values. The instrument used is a creative thinking ability description test that considers validity, reliability, difficulty level, and distinguishing power. In the experimental class, the average score of creative thinking ability was 83.77, while the control class obtained a score of 74.50. The data of both classes were normally distributed and homogeneous. The polled variance t-test was used at the 5% level to assess the data related to Creative Thinking Ability. 4.813 is the result of the analysis of creative thinking ability. This shows that there is a relationship between their ability to think creatively and the causal model combined with character values.